EFFECT OF ADAPTIVE ATHLETIC ON SUBLIMATION NON VERBAL AGGRESSIVE BEHAVIOR IN PROBLEMS EMOTION AND BEHAVIOR - Ristianti, Ilmi; Setiawan, Atang; Wibowo, Wahyu Setyo (JASSI ANAKKU, 2020)
This study aims to determine the effect of adaptive athletics on the sublimation of non¬verbal aggressive behavior in children with emotional and behavioral disorders at SLB Bhina Putera Surakarta. This research needs to be done because non-verbal aggressive behavior is a destructive behavior that interferes with the child's learning process so that the child will have difficulty following the learning. This research is an experimental study using the Single Subject Research (SSR) approach. The research design used is the A-B-A 'design. The research subject is a child with emotional and behavioral disorder in sixth grade at SLB Bhina Putera. Collecting data by conducting observation on students using non-verbal aggressive behavior instruments. Then the data obtained were analyzed through descriptive statistics and displayed in graphs and tables. The components analyzed in this study were the analysis in conditions and between conditions. The results showed that there was a positive influence on the sublimation of children's non-verbal aggressive behavior after being intervened with adaptive athletics. The positive effect is indicated by an decrease in the mean level of the three phases. Starting from the baseline-1 phase (A1) with a mean level of 95,3%, the intervention phase (B) of 77,4%, and the baseline-2 phase (A2) of 52,7%. Then, the magnitude of the effect of intervention using adaptive athletics can be seen from the percentage overlap. The smaller the overlap percentage, the better the intervention effect. The result of overlap percentage is 11.1%. Thus, adaptive athletics influenced the sublimation of children's non-verbal aggressive behavior in SLB Bhina Putera by 88.9%.